If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -7x = 1 + -8x Solving 6 + -7x = 1 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 6 + -7x + 8x = 1 + -8x + 8x Combine like terms: -7x + 8x = 1x 6 + 1x = 1 + -8x + 8x Combine like terms: -8x + 8x = 0 6 + 1x = 1 + 0 6 + 1x = 1 Add '-6' to each side of the equation. 6 + -6 + 1x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = 1 + -6 1x = 1 + -6 Combine like terms: 1 + -6 = -5 1x = -5 Divide each side by '1'. x = -5 Simplifying x = -5
| 1+7p=7+8p | | n-5(3n+1)=7 | | 11x+6=10x+153 | | 4(n-59)-41=35 | | 3+3x=75 | | 3.1k-8.94=2.7k+7.7 | | 11+6=-10+153 | | 2(x-8)+3=6 | | 14+2x=22 | | 2=8v+8-8v | | (x+6i)=(3-i)+(4-2yi) | | 8xy*7xy^2= | | -10+7x=3x+34 | | 3/8x-1/2=7/4 | | 2x-20=3x+20 | | 1/8x+1/8(7x+16)=-5/6 | | 2(m-5)-8=-2 | | 6x+16-12x=24+2x | | 3y-7=-y+-19 | | 24x^2+3=0 | | (2x+22)(x-5)=0 | | q/4-2=8 | | -1x+2y=-6 | | -22-(x+6)=4x-4 | | (x+5)-4=x+44 | | 3w+4w+3y-11y+10x+5x= | | 28=8(x-7) | | 7-3x=51+8x | | -74=24-7z | | (2x+22)(x-5)=130 | | 4x^2-3x+8=35 | | 7x+6-3(x+1)=-4x-6 |